Green microwave versus conventional synthesis, crystal structure of 1-(4-(Benzothiazol-2-yl)piperazin-1-yl)-2-(4-phenyl-1H-1, 2, 3-triazol-1-yl)ethenone and HS-Analysis. Issue 1 (1st January 2020) - Said, Musa A.; Messali, Mouslim; Rezki, Nadjet; Al-Soud, Yaseen A.; Aouad, Mohamed R.
Abstract : This study reports an efficient eco-friendly microwave assisted synthesis of 1-(4-(benzothiazol-2-yl)piperazin-1-yl)-2-(4-phenyl-1 H -1, 2, 3-triazol-1-yl)ethanone (4 ) through the click cyclocondensation of 2-azido-1-(4-(benzo[ d ]thiazol-2-yl)piperazin-1-yl)ethanone (3 ) with phenyl acetylene. The synthesis was carried out under optimized copper catalyst copper(II) sulfate pentahydrate/sodium ascorbate, t -BuOH/water (1:1, v/v) to afford the regioselective 1, 4-disubstituted 1, 2, 3-triazole isomer. The reactions were greatly accelerated using microwave irradiation. The new designed 1, 2, 3-triazole was fully characterizid by IR, NMR, MS spectral data and X-ray diffraction. The crystal structure of 4 demonstrated a conventional chair conformation for the piperazine ring. Interesting Hirshfeld Surface Analysis (HAS) was conducted showing clear agreement with the XRD analysis.